Chamaecytisus palmensis (Christ) Hutch. cultivated in Sardinia with different planting density - Vargiu M.; Spanu E. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
A population of Chamaecytisus palmensis (Christ) Hutch. was evaluated for its homogeneity and forage production. 300 cuttings were planted in September 2013 in 3 m spaced rows, at a row distance of 0.5 m and 1 m, with a resulting density of 6600 and 3300 plants per hectare. In the first year the trial was irrigated until March, 2014 owing to winter drought. The plant development was rather slow: planting was very water exigent and in 2015 suffered from winter cold. First utilization was possible in February 2015 and other four samplings were made until September 15, 2016, attaining an overall yields of 1 t ha-1, with a better production in the highest plant density thesis. Regarding biological cycle and morphological traits, the Chamaecytisus population showed a large variability.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)